2008
DOI: 10.1016/j.cattod.2008.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Selective H–D exchange catalysed by aqueous phase and immobilised Pd nanoparticles

Abstract: Publication informationCatalysis Today, 139 (3): 154-160Publisher Elsevier Item record/more information http://hdl.handle.net/10197/4001 Publisher's statementThis is the author's version of a work that was accepted for publication in Catalysis Today. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be reflected in this document. Changes may have been made to this work since it was submitted for publicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…12). 66 This MWCNT/Pd-DMAP nanocomposite was tested in the Suzuki cross-coupling of 4-iodobenzoic acid with phenylboronic acid. This system was then compared to the MWCNT/complex composite that was prepared by adding the Pd(DMAP) 4 (OH) 2 complex to thiolated MWCNTs.…”
Section: Carbon Nanotube-based Nanocatalystsmentioning
confidence: 99%
“…12). 66 This MWCNT/Pd-DMAP nanocomposite was tested in the Suzuki cross-coupling of 4-iodobenzoic acid with phenylboronic acid. This system was then compared to the MWCNT/complex composite that was prepared by adding the Pd(DMAP) 4 (OH) 2 complex to thiolated MWCNTs.…”
Section: Carbon Nanotube-based Nanocatalystsmentioning
confidence: 99%
“…Under this premise, the efficiency of the exchange process for 4-aminopyridines would be attributed to the increased pyridine basicity in general base catalysis, increased stability of the pyridinium ylides III upon deprotonation, or a shift from general base catalysis to an internal return limited process, with no significant general base catalysis and slow dissociation of a hydrogen-bonded ylide III-conjugate acid complex, as a consequence of the reduced acidity of the pyridinium conjugate acid. 18d A profile of reactivity dependent upon aminopyridine basicity and proceeding in equilibrium via pyridinium ylide III would, broadly speaking, explain the trends observed in this work (Table 3), such as reduced exchange in 4-amino-2-chloropyridine ( 18), 4-aminopyrimidine (19), and 2-aminopyrazine (20), but clearly other factors are involved. For example, D incorporation at C-2 (80%) vs. C-6 (12%, Table 1) of 3-aminopyridine (pK aH 5.98) indicates a role of ylide III stability, which could also be in evi-…”
Section: Letter Syn Lettmentioning
confidence: 66%
“…16 Many recent efforts have been directed towards the efficient H/D exchange of pyridine derivatives. [20][21][22][23][24][25][26][27] A highly site-selective one-step α-labelling of pyridines and N-heteroaromatic compounds has been described using deuterium gas and a rhodium or ruthenium catalyst. 28 Furthermore, it has been remarked that a 4-pyrrolidino group accelerates H/D exchange at all pyridine positions.…”
mentioning
confidence: 99%
“…In 2008, Sullivan et al reported the use of 3.4 nm Pd NPs immobilized on multiwalled carbon nanotubes (MWCNTs) for catalyzing in aqueous medium H−D exchange on aromatic C− H bonds of 4-dimethylaminopyridine (DMAP) with a selectivity for the α position to N. 128 The authors studied the effect of the temperature on the reaction and showed that at higher temperatures (80 °C), the reaction rate increased but led to a higher deuteration degree in the β position as a side reaction. Other substrates containing a pyridine ring were tested in the H/ D exchange reaction at 50 °C (see Table 1).…”
Section: H−d Exchange Catalyzed By Metal Npsmentioning
confidence: 99%